Fog robotics-based intelligence transportation system using line-of-sight intelligent transportation - Poornima, E.; Muthu, BalaAnand; Agrawal, Ruchi; Kumar, S. Pradeep; Dhingra, Mallika; Asaad, Renas Rajab; Jumani, Awais Khan (Multimedia tools and applications, 2025)
Intelligent Transportation System (ITS) idea was developed to improve road safety, traffic management efficiency, and environmental preservation. The fog- robotics Based Intelligent Transportation Systems integrate Internet of Vehicles (IoV) devices to Fog Computing (FC) centers, which process the data. On the other hand, providing massive data from widely distant devices causes network overhead and bottlenecks in Autonomous Driving and a drain on Energy Management. To fill this research gap, fog-robotics-based intelligent transportation systems are proposed to cover the line-of-sight direction for path adopting self-directed intelligent transportation. The Intelligent Transportation Systems with FC Techniques work towards the Fog Robotics Platform for making efficient fog- robotics Transportation Systems. The Proposed System has two functionalities; firstly, the analysis of automatic Fog- robotics transportation systems is introducing decentralized wireless sensor transfer assisted flocking autonomous driving for energy management of fog- robotics transportation systems. It Shows the Sensor activities as per the “scanning of the roadside meter.” It enumerates speed control. Secondly, Artificial Intelligence Enabled Intelligent speed assistance is formed based on Vehicle Infrastructure Integration (VII). This Vehicle infrastructure integration is used to show the Smart highway, which is adaptable with the fog- robotics Transportation Systems. Although the formation of “Digital modeling and fabrication framework” procedural aspect employed to connect the “Fog- robotics Transportation Systems” and “Vehicle infrastructure integration.” This Artificial Intelligence configuration is used to Enabled Intelligent speed assistance for controlling the car for their atmosphere. Finally, these rely on are consolidated with the position/navigation system, and the vehicle detection ratio is analyzed with the vehicle efficiency and economic activity for intelligent speed assistance.